2022
DOI: 10.1136/bmjgh-2022-009904
|View full text |Cite
|
Sign up to set email alerts
|

Digital marketing of formula and baby food negatively influences breast feeding and complementary feeding: a cross-sectional study and video recording of parental exposure in Mexico

Abstract: BackgroundThere is little evidence of the association between digital marketing of formula and baby food and infant and young child feeding (IYCF) practices.ObjectiveAssess parents’ exposure to digital marketing of formula and baby food for children <2 years and its association with the purchase and IYCF practices in Mexico.MethodsParents ≥18 years recruited from a market research panel completed an online survey (n=1074) and capture-on-screen (n=95) between December 2020 and January 2021. Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…This concurs with results from a study that reported women with mobile phones to have 75% lower odds of EBF which was attributed to the distractive effect of mobile phones on breastfeeding women [53]. In addition, a study found that mothers who viewed more adverts about infant formula in media had lower odds of breastfeeding than their counterparts who viewed less or no adverts, as the latter perceived infant formula as the most convenient option for child feeding [54]. This is supported by the fact that the tendency to exclusively breastfeed mainly depends on the speci city of the content shared on media.…”
Section: Discussionsupporting
confidence: 87%
“…This concurs with results from a study that reported women with mobile phones to have 75% lower odds of EBF which was attributed to the distractive effect of mobile phones on breastfeeding women [53]. In addition, a study found that mothers who viewed more adverts about infant formula in media had lower odds of breastfeeding than their counterparts who viewed less or no adverts, as the latter perceived infant formula as the most convenient option for child feeding [54]. This is supported by the fact that the tendency to exclusively breastfeed mainly depends on the speci city of the content shared on media.…”
Section: Discussionsupporting
confidence: 87%
“…South Africa has already passed this regulation, and the breastmilk substitutes are no longer promoted in some provinces, including Limpopo. Baby foods, which are defined as commercially prepared foods and beverages for infants, are linked to a drop in prolonged breastfeeding and poor IYCF practices [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children under 2 years of age were invited to participate after answering an online survey about their children’s eating habits and digital marketing of commercial milk formula and baby foods, explained elsewhere [ 24 ]. Other key actors were identified based on their influence on breastfeeding and infant feeding issues, their professional or academic networks, in addition to their presence in social media.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we documented that 93.9% of Mexican parents of young children and with access to internet are exposed to digital marketing of commercial milk formula and baby foods, and those more frequently exposed were 62% less likely to exclusively breastfeed within the first 6 months and more likely to give their children processed foods and sugary drinks [ 24 ]. The WHO recommends ending the inappropriate promotion of products that contain added sugars, salt, trans fats, additives, or ingredients not suitable for infants and young children [ 25 ], including follow-up and growing-up milks which are in the Code’s scope [ 26 ].…”
Section: Introductionmentioning
confidence: 99%